2016
DOI: 10.1002/smll.201600064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultrasmall Cu2O Nanocubes and Octahedra with Tunable Sizes for Facet-Dependent Optical Property Examination

Abstract: Size-tunable small to ultrasmall Cu2 O nanocubes and octahedra are synthesized in aqueous solution without the introduction of any surfactant. These nanocrystals provide strong evidence of the existence of facet-dependent optical absorption properties of Cu2 O nanoparticles, showing nanocubes always have a more redshifted absorption band than that of octahedra having a similar volume by about 15 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 29 publications
5
89
0
Order By: Relevance
“…[9][10][11][12][13][14][15] As the ultrathin layer has dissimilar band structures for different crystal faces it meanst hat light of somewhat differentw avelengths is absorbed by particles of variouss hapes, accounting for the observedf acet-dependent opticalp roperties of Cu 2 Oa nd other semiconductor crystals. [7,11,[16][17][18] To verify that the facet-dependent electrical-conductivity phenomenon is broadly observable in semiconductors, electrical-conductivity measurementsh ave been made on four different faces of Si wafers, which revealed that the (111)a nd (112) surfaces are highly conductive. [19] The results are consistent with previous DFT calculations showing metal-like band structuresf or these two Si surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] As the ultrathin layer has dissimilar band structures for different crystal faces it meanst hat light of somewhat differentw avelengths is absorbed by particles of variouss hapes, accounting for the observedf acet-dependent opticalp roperties of Cu 2 Oa nd other semiconductor crystals. [7,11,[16][17][18] To verify that the facet-dependent electrical-conductivity phenomenon is broadly observable in semiconductors, electrical-conductivity measurementsh ave been made on four different faces of Si wafers, which revealed that the (111)a nd (112) surfaces are highly conductive. [19] The results are consistent with previous DFT calculations showing metal-like band structuresf or these two Si surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The successful synthesis of Cu 2 O, Ag 2 O, PbS, and Ag 3 PO 4 crystals with tunable shapes and sizes has revealed that they possess various facet‐dependent properties, including electrical conductivity, photocatalytic activity, and optical properties . In particular, the discovery that Cu 2 O nanocrystals display size‐ and facet‐dependent light absorption and emission properties suggests that such novel phenomena may be observable in other semiconductor materials . To extend the development of metal oxides to chalcogenides, lead sulfide (PbS) nanocrystals with tunable shapes have been synthesized in aqueous solution by adjusting the reaction equilibrium through the addition of nitric acid .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In particular, the discoveryt hat Cu 2 On anocrystals display sizeand facet-dependent light absorption and emission properties suggestst hat such novel phenomena mayb eo bservable in other semiconductor materials. [2,6] To extend the development of metal oxidest oc halcogenides, lead sulfide (PbS) nanocrystals with tunable shapesh ave been synthesized in aqueous solution by adjustingt he reactione quilibrium through the addition of nitric acid. [7,8] It is therefore natural to consider the preparation of even more challengingl ead selenide nanocrystals, and evaluate their opticalp roperties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] These interesting semiconductor properties can be explained in terms of the presence of an ultrathin surface layer having varying degrees of band bending for different surface planes.T his effect controls the relative obstacle of charge transport through asemiconductor crystal depending on the points of electrical contacts.S uch af eature is highly useful for electronic component design. [13][14][15][16][17][18] Since facet effects are observable in many semiconductor materials,i ti s highly interesting to examine possible existence of facetdependent electrical properties of silicon. [7][8][9][10][11][12][13] Furthermore,this thin layer with dissimilar band structures for different surface planes also gives rise to the observed facet-dependent optical absorption and emission properties in semiconductor nanocrystals and quantum nanostructures that has been recognized recently.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Furthermore,this thin layer with dissimilar band structures for different surface planes also gives rise to the observed facet-dependent optical absorption and emission properties in semiconductor nanocrystals and quantum nanostructures that has been recognized recently. [13][14][15][16][17][18] Since facet effects are observable in many semiconductor materials,i ti s highly interesting to examine possible existence of facetdependent electrical properties of silicon. Silicon has largely been the material of choice for integrated circuit fabrication, and novel photonic devices also use Si nanostructures.…”
mentioning
confidence: 99%